Competition and Corporate Performance. - Nickell, S (1996)
Are people right to think that competition improves corporate performance? The author's investigations indicate first that there are some theoretical reasons for believing this hypothesis to be correct but they are not overwhelming. Furthermore, the existing empirical evidence on this question is weak. However, the results reported here, based on the analysis of around 670 U.K. companies, provide some support for this view. Most important, the author presents evidence that competition, as measured by increased numbers of competitors or by lower levels of rents, is associated with a significantly higher rate of total factor productivity growth.